Blue- versus green-absorbing anion channelrhodopsins, essential tools in optogenetics, differ fundamentally in gating mechanisms - Oleg A. Sineshchekov; Elena G. Govorunova; Hai Li; Yumei Wang; John L. Spudich (Proceedings of the National Academy of Sciences, 2026)
The genomes of many protists encode at least one pair of spectrally distinct cation or anion channelrhodopsins. Two cation channelrhodopsins (CCRs) initiate different transduction cascades in Chlamydomonas . Two Guillardia anion channelrhodopsins (ACRs) are emerging molecular tools for optical inhibition of neuronal firing, but their functions in the source organism remain unclear. Furthermore, Gt ACR2 remains poorly investigated compared to Gt ACR1, although its faster channel kinetics makes it preferable for optogenetic control of neurons firing at high frequencies. Using patch-clamp recording in mammalian cells, photochemical characterization of purified proteins, and mutational analysis, we found a fundamental mechanistic difference between blue-absorbing Gt ACR2 and green-absorbing Gt ACR1, which may indicate different functions in the alga. Gt ACR2 exhibits only one channel gating mechanism, unlike Gt ACR1, in which we had detected two mechanisms. Gt ACR2’s faster channel closing strongly depends on the holding voltage, and its photocycle shows considerable intermediate reversibility. Photocurrents evoked by continuous light pulses reflecting secondary photochemistry reveal further differences between Gt ACR1 and Gt ACR2. Mutagenetic replacement of five divergent Gt ACR2 residues with those of Gt ACR1 reproduced the latter’s spectral sensitivity and slow biphasic channel closing. Only one Gt ACR2 mutation, R129C, which individually caused the most substantial red shift, restored the gating mechanism typical of Gt ACR1. Gt ACR2, but not Gt ACR1, exhibited a change in the F − /Cl − relative permeability during the single-turnover photocycle. Comparison to Chlamydomonas CCRs and ACRs from other protists suggests that these differences between blue- and green-absorbing ChRs are a general rule, which can guide further development of optogenetic tools.